2009
DOI: 10.1016/j.cmet.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210 Controls Mitochondrial Metabolism during Hypoxia by Repressing the Iron-Sulfur Cluster Assembly Proteins ISCU1/2

Abstract: Summary Repression of mitochondrial respiration represents an evolutionarily ancient cellular adaptation to hypoxia and profoundly influences cell survival and function; however, the underlying molecular mechanisms are incompletely understood. Primarily utilizing pulmonary arterial endothelial cells as a representative hypoxic cell type, we identify the iron-sulfur cluster assembly proteins (ISCU1/2) as direct targets for repression by the hypoxia-induced microRNA-210 (miR-210). ISCU1/2 facilitate the assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
575
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 594 publications
(615 citation statements)
references
References 35 publications
36
575
4
Order By: Relevance
“…Induction of apoptosis by miR-210 is consistent with very recent reports indicating that miR-210 represses the growth of tumor xenograft from head, neck and pancreatic cancer cells 12 and increases apoptosis in pulmonary arterial endothelial cells (HPAECs) in vitro. 18 While we confirmed that the transcript coding for E2F3, a key protein in the cell cycle, is a functional target of miR-210, 11 we also found that miR-210 induced cell death associated with activation of caspases, whereas E2F3 siRNA did not. Indeed, E2F3 silencing and miR-210 overexpressions led to very distinctive expression patterns, thus suggesting that the effect of miR-210-induced cell death was rather mediated by targeting other transcripts.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Induction of apoptosis by miR-210 is consistent with very recent reports indicating that miR-210 represses the growth of tumor xenograft from head, neck and pancreatic cancer cells 12 and increases apoptosis in pulmonary arterial endothelial cells (HPAECs) in vitro. 18 While we confirmed that the transcript coding for E2F3, a key protein in the cell cycle, is a functional target of miR-210, 11 we also found that miR-210 induced cell death associated with activation of caspases, whereas E2F3 siRNA did not. Indeed, E2F3 silencing and miR-210 overexpressions led to very distinctive expression patterns, thus suggesting that the effect of miR-210-induced cell death was rather mediated by targeting other transcripts.…”
Section: Discussionmentioning
confidence: 47%
“…Accordingly, SDHD inhibition mimicked several miR-210-mediated cellular effects, including alteration of mitochondrial ultrastructure (Figure 5a), decrease of cell viability ( Figure 5b) and activation of caspases ( Figure 5c). Our findings appear particularly interesting in the light of the report published during the preparation 18 and revision 24,31 of this paper, showing that miR-210 also targets the transcript coding for ISCU1/2. ISCU1/2 facilitate the assembly of ironsulfur clusters that are incorporated into enzymes involved in energy production, including mitochondrial respiratory complexes I, II and III.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…19,20 HIF-1a also negatively regulates TCA cycle enzymes, indirectly through inducing miR120. 21,22 In this report, we describe a previously unrecognized metabolic response to low-dose radiation. By using an integrated approach, we demonstrate that low-dose radiation induces a metabolic shift from oxidative phosphorylation to aerobic glycolysis leading to increased radiation resistance in both cell and animal models.…”
mentioning
confidence: 86%
“…In many regards, PH disease progression mirrors tumorigenesis in relying on a metabolic switch from mitochondrial oxidative phosphorylation to cytoplasmic glycolysis (known as the Warburg effect) (2) to provide a survival advantage to highly proliferating cells (11). The hypoxia-dependent miR-210 is one of several miRNAs implicated in this metabolic rewiring (12)(13)(14). Among its pleiotropic actions, miR-210 was found to repress directly the iron-sulfur cluster assembly proteins (ISCU1/2) essential for mitochondrial respiration, leading to Fe-S deficiencies and PH development.…”
Section: Metabolism and Proliferationmentioning
confidence: 99%